STUDI PERANCANGAN LAMBUNG SMALL WATERPLANE AREA TWIN HULL (SWATH) KAPAL PROTECTOR DENGAN SISTEM UNMANNED SURFACE VEHICLE (USV) UNTUK PERAIRAN AMBALAT - Bahatmaka, Aldias; Hadi, Eko Sasmito; Mulyatno, Imam Pujo (Diponegoro University, 2014)
Indonesia is a maritime country with potential natural resources . One is Ambalat Island. Ambalat is a sea block with an area covering 15,235 square kilometers located in the Sulawesi Sea and the Makassar Strait or near the extension of land between Malaysia Sabah and East Kalimantan, Indonesia. One point Ambalat keep mine in the potential reserves 764 million barrels of oil and 1.4 trillion cubic feet of gas . But the problem that occurs is increasingly rapine of natural quarry . Additionally, when Malaysia had initially claimed that Indonesian waters 70 miles from the border Sipadan island beach and Ligitan , Malaysia to expand its territory as far as 2 miles. Thereby reducing area of Indonesia. It happened due to the lack of maintenance of the maritime territory of the Republic of Indonesia (NKRI), especially in border areas like Ambalat Island. Based on this,it is necessary technology innovations especially warship design that could be a solution as alusista ( main instrument of defense systems ) Indonesian Navy in maintaining maritime Homeland.In this study, the chosen design is the type of hull SWATH (Small waterplane Area Twin Hull) with minimal cross-sectional area of the hull at sea level and maximize the stability of the sea at high speed so that the hull swath able to cover the weakness in the monohull and catamaran, hull which means it has the stability very well and is able to maneuver at high speeds. The operating system used is the Unmanned SurfacesVehicle (USV) or the ship without crew.This design results obtained swath protector hydrostatic analysis , stability , and seakeeping and the lines plan and general arrangement . By using the design method of optimization comparisons from ship references. Obtained the ship's main dimensions are Loa = 11,00 m , LWL = 8.976 m , B = 6.00 m , H = 3.80 m , T = 1.60 m . The swath Protector can sail trough Ambalat Island of 469 sea miles with a tank capacity FOT = 1,73 m3 , DOT = 2,40 m3 , LOT = 2,40 m3 . And for hydrostatic calculations , the ship has a displacement of 23.66 tons with block coefficient ( Cb ) = 0.22 and LCB position = 4.64 . Stability analysis results indicate that the vessel has a maximum GZ value occurs in the condition I followed the 2,722 m at 2,721 m the condition II , and III is 2.719 m . And the value of MG occurred in the 5,701 m , III conditions that led to the vessel having the fastest time to return to the upright position . Resistances Calculation results with analysis software at full speed V = 40 knots , has a resistances value is 64.14 kN and power is 1642.30 kW or 2359.94 HP with a slender body method . Based on the calculation of ship resistance , the chosen propulsion is a water jet machine as much as the two inboard diesel power respectively with each power is 1000 kW / 1340HP.